Rising to the Challenge? The State of the Art and Future Research Directions of Polish Environmental Sociology - Tusznio, Joanna; Matczak, Piotr; Rechciński, Adam; Choryński, Adam; Niedziałkowski, Krzysztof (My University, 2023)
Environmental sociology has been developing since the 1970s; however, it only recently became institutionalized in Poland with the establishment of a respective section in the Polish Sociological Association. We argue that environmental sociology in Poland and the broader area of Central and Eastern Europe has made an important contribution to international research on relations between humanity and nature in the Anthropocene. This paper presents the current state of the art in Polish environmental sociology and discusses future research questions. Our contribution is based on a literature review and the results of a workshop with Polish environmental sociologists. Future research areas discussed in this paper emerge from the following five main thematic domains: (I) social aspects of nature conservation; (II) environmental groups and movements; (III) sustainable development and the participation of local communities in rural and urban areas; (IV) environmental risks and threats and (V) and energy and society.
Keywords: Anthropocene; environmental sociology; future research; people and nature; sociology of natural resources